Advances in evaluating the fetal skeleton - Noel AE; Brown RN (Dove Medical Press, 2014)
Ann-Edwidge Noel, Richard N BrownDivision of Maternal Fetal Medicine, Department of Obstetrics and Gynecology, McGill University, Montreal, QC, CanadaAbstract: In this review, we discuss aspects of the prenatal diagnosis of fetal skeletal malformations, concentrating on the advantages offered by different imaging techniques and the approaches that are of value in evaluating a suspected skeletal dysplasia. We also briefly address the findings in some of the commoner malformations of the fetal skeleton that may be encountered.Keywords: prenatal diagnosis, skeletal dysplasia, ultrasound, fetal imaging, osteodysplasia, chondrodysplasia, dysostosis